A Psychosemantic Study of Compensation Psychological Defense Mechanism in the Novice Military Leaders - Khraban, Tetyana; Khraban, Ihor (Lesya Ukrainka Volyn National University, 2020)
The aim of the article is to study the formative impact of the defense mechanism “compensation” on the leader’s personality. The research is based on the axiological semantic research method created due to the development and application of experimental psychosemantics to the issue of leadership. An experiment was conducted with the view of confirming the fact of impact of the defense mechanism “compensation” on the leader’s personality formation. This experiment involved 30 students undergoing leadership training for tactical officers at the Heroiv Krut Military Institute of Telecommunications and Information Technologies. A test-questionnaire was created to experimentally substantiate the reliability of the proposed conjecture. At the outset of the experiment, the participants were asked to note in the test-questionnaire the basic postulates they rely on when forming relationships in the military community. For the purpose of creating a relaxed atmosphere the postulates (60 units) were presented in the form of posts (quotes and aphorisms) which are most often posted on social media pages. Based on the methods of psychological subjective semantics and psychosemantics, we established the predominance of a certain form of defence mechanism “compensation”. Then followed the assessment of the leadership role preferences displayed by the participating pilot students, this providing the basis for drawing conclusions as regards the tendency for a particular form of leadership. Matching of the obtained results revealed correlations between mental reflections of various phenomena. Although correlational study has a lower degree of confidence in predicting cause and effect, it can provide strong indications that relationships exist. Results and discussions. The defense mechanism “direct compensation” correlates with the kind of “fighter” leader, “overcompensation” correlates with the kind “father”, “decompensation” correlates with the kind “tyrant”. To conclude, trend to use a certain type of defense mechanism affects the acceptance and assimilation of a certain role type of leader. In addition, the use of information which are most often posted by social media users on their personal accounts as a content for the test-questionnaire allows us to conclude about the possibility of using social media account to determine the psychological type of personality by analyzing posts, likes and comments.
Keywords: experimental psychosemantics; leadership; psychological defense mechanism